ANALISIS FATWA MUI TAHUN 2007 TENTANG SEPULUH KRITERIA ALIRAN SESAT - Anung Al Hamat (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2017)
Indonesian Muslims are the most numerous in number. They  are majority. But the irony, it is also so easy for distorted and perverted sects to grow and develop in this country. There have been many communities contaminated by preverted insights that can harm both in religious life nor the State. In order to control and fortify the creed of muslims, then MUI (the Muslims scholars of Indonesia) issues  decision or fatwa about Ten Criteria of Perverted Sects.The focus problem in this research is describing and analysing the ten criteria of a perverted sects decided by MUI on Novemver 6, 2017 in the aspect of thought and law. So it can be excavated various preversions in the criteria that have been decided by the Center of MUI along with the status of law. The expectation for the next, the public can be careful and wary from preverted insight, and so they were freed from various forms of error and deviations.